Differences in tolerability of pirfenidone between elderly and younger patients with idiopathic pulmonary fibrosis - Sakayori M; Terada J; Abe M; Hirasawa Y; Suzuki K; Yoshioka K; Tsushima K; Tatsumi K (Dove Medical Press, 2019)
Masashi Sakayori,1 Jiro Terada,1 Mitsuhiro Abe,1 Yasutaka Hirasawa,1 Kenichi Suzuki,1 Keiichiro Yoshioka,1 Kenji Tsushima,2 Koichiro Tatsumi11Department of Respirology, Graduate School of Medicine, Chiba University, Chiba 260-8670, Japan; 2Department of Pulmonary Medicine, International University of Health and Welfare, School of Medicine, Chiba 286-8686, JapanPurpose: Although pirfenidone (PFD) is a key drug for the treatment of idiopathic pulmonary fibrosis (IPF), differences in tolerability between elderly and young patients remain unclear. This study aimed to investigate age-related differences in adverse drug reactions to PFD and to evaluate whether patient age influences the safety and tolerability of PFD in clinical practice.Patients and method: One hundred fifty-four patients with IPF were treated with PFD in our institution between May 2009 and April 2017; these patients were classified into 2 groups on the basis of age: ≥75 years of age (elderly patients) and <75 years of age (younger patients). In each group, the clinical course, laboratory data, radiographic findings, adverse events, and tolerability of PFD at 6 months and 1 year after administration were retrospectively analyzed.Results: Among the 120 patients examined in this study, 31 patients (26%) were ≥75 years of age. The continuation rate of PFD at 1 year in the elderly patient group was significantly lower (n=11 [35%] vs 57 [64%], p=0.007) than in the younger patient group. Regarding adverse drug reactions to PFD, the incidence of gastrointestinal disorders including anorexia (n=24 [77%] vs 40 [45%], p=0.002) and the discontinuation caused by gastrointestinal disorders (n=11 [35%] vs 13 [15%], p=0.019) were significantly higher in elderly patients than those in younger patients. However, with the exception of gastrointestinal disorders, other adverse drug reactions did not significantly differ between elderly and younger patients.Conclusions: Compared with younger patients, elderly patients with IPF had a higher incidence of gastrointestinal disorders, along with an increased discontinuation rate of PFD. More careful management of gastrointestinal disorders may be required to ensure continuation of PFD in elderly patients.Keywords: idiopathic pulmonary fibrosis, pirfenidone, tolerability, adverse drug reactions